Lessons learnt from the implementation of same-day discharge after percutaneous coronary intervention. Issue 6 (November 2019) - Chen, Yingyan; Marshall, Andrea P.; Lin, Frances
Abstract: Background: Change in healthcare organisations is constant and requires adequate resources for effective implementation. Same-day discharge after percutaneous coronary intervention has been found to be no different from the patients who stayed overnight after procedure; however, its uptake remains low. Objectives: The aim of the study was to identify what factors helped or hindered the implementation of same-day discharge. Methods: This interpretive study was conducted in a cardiac catheterisation suite of an Australian tertiary hospital between June and December 2016. Semistructured individual interviews with 26 healthcare professionals were conducted to explore the factors that influenced the implementation. A deductive approach to content analysis was guided by the theoretical domains framework. Findings: Five domains, including beliefs about consequences, professional role and identity, resources, behaviour regulation, and optimism, were identified which were strongly related to the factors that impacted the implementation. The findings showed that participants believed same-day discharge benefits while also concerning about its safety and holding different opinions on eligibility criteria. The findings also showed that participants' involvement in the change process varied with no clear roles and responsibilities and that their understanding about same-day discharge evidence and the guideline also differed. Lack of dedicated resources was also identified as the hindrance to the implementation. Behaviour regulation domain depicted how communication was managed and how the care for same-day discharge patients was improved. Despite several issues identified, participants were optimistic with achievement. Discussion and conclusion: This study has provided valuable insight into the factors that influenced the implementation, which will inform policymakers when designing interventions for future improvement. Plan for change and involvement of all stakeholders along with dedicated resources including time, people, and change management expertise are essential if hospitals want to see the success of change.